Uninterruptible power supply topology based on single-phase matrix converter with active power filter functionality - Mohamad Rawi, Muhammad Shawwal; Baharom, Rahimi; Mohd Radzi, Mohd Amran (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This study introduces a novel uninterruptible power supply (UPS) configuration that integrates active power filter (APF) capabilities within a single-phase matrix converter (SPMC) framework. Power disruptions, particularly affecting critical loads, can lead to substantial economic damages. Historically, conventional UPS systems utilized dual separate converters to function as a rectifier and an inverter, without incorporating any power factor correction (PFC) mechanisms. Such configurations suffered from diminished power density, compromised reliability, and spatial limitations. To address these issues, this research proposes an enhanced UPS design that incorporates APF features into the SPMC. The focus of this investigation is on the efficiency of alternating current (AC) to direct current (DC) conversion and the reverse process utilizing this advanced UPS model. The SPMC is selected to supplant the rectifier and inverter units traditionally employed in UPS architectures. A novel integrated switching strategy is formulated to facilitate the operation of the UPS in either rectifier (charging) or inverter (discharging) modes, contingent upon the operational state. The performance and efficacy of the devised circuit design and switching technique are substantiated through simulations conducted in MATLAB/Simulink 2019 and empirical evaluations using a test rig. The findings demonstrate that the voltage generated is sinusoidal and synchronized with the supply current, thereby minimizing the total harmonic distortion (THD) and enhancing both the power factor and the transition efficiency of the UPS system between its charging and discharging states.